2007
DOI: 10.1182/blood-2006-09-047068
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of immunohistochemically defined germinal center phenotype in diffuse large B-cell lymphoma patients treated with immunochemotherapy

Abstract: Germinal center (GC) and non-GC phenotypes are predictors of outcome in diffuse large B-cell lymphoma (DLBCL) and can be used to stratify chemotherapy-treated patients into low-and high-risk groups. To determine how combination of rituximab with chemotherapy influences GCassociated clinical outcome, GC and non-GC phenotypes were identified immunohistochemically from samples of 90 de novo DLBCL patients treated with rituximab in combination with CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
159
4
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(185 citation statements)
references
References 31 publications
13
159
4
9
Order By: Relevance
“…These results suggest that the SH3BP5 and LMO3 protein expressions may be related to the molecular pathogenesis of DLBCL and that rituximab addition can overcome the negative effect of the expression of these two proteins. Similar data regarding the loss of prognostic value for DLBCL patients treated with R‐CHOP have been reported 12, 13, 14. Rituximab mediates drug‐induced apoptosis via down‐regulation of several signaling pathways and chemosensitization of non‐Hodgkin's lymphoma B‐cells 15.…”
Section: Discussionsupporting
confidence: 68%
“…These results suggest that the SH3BP5 and LMO3 protein expressions may be related to the molecular pathogenesis of DLBCL and that rituximab addition can overcome the negative effect of the expression of these two proteins. Similar data regarding the loss of prognostic value for DLBCL patients treated with R‐CHOP have been reported 12, 13, 14. Rituximab mediates drug‐induced apoptosis via down‐regulation of several signaling pathways and chemosensitization of non‐Hodgkin's lymphoma B‐cells 15.…”
Section: Discussionsupporting
confidence: 68%
“…Nyman et al 25 demonstrated that patients with germinal center B-cell-like DLBCL (defined by Hans algorithm) had better clinical outcomes than those with nongerminal center B-cell-like DLBCL phenotypes if treated with systemic chemotherapy but not if treated with rituximab chemotherapy. This suggests that the incorporation of rituximab might eliminate the prognostic value of germinal center B-cell-like versus nongerminal center B-cell-like DLBCL as defined by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the incorporation of rituximab might eliminate the prognostic value of germinal center B-cell-like versus nongerminal center B-cell-like DLBCL as defined by IHC. 25 These investigators also retrospectively subtyped 88 consecutive rituximab-CHOP-treated DLBCL patients with modified Hans criteria, in which staining for forkhead box P1 was added to the algorithm. 26 Patients with an activated B-cell-like phenotype had a significantly worse outcome than patients with a nonactivated B-cell-like phenotype (3-year failure-free survival, 63% vs 82%; P ¼ .048; OS, 69% vs 85%; P ¼ .110).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The relevance of these findings is that the activated blood B-cells subtype is associated with a significantly worse clinical outcome even after the introduction of immunochemotherapy. 3,[6][7][8][9] Therefore, the molecular subtyping of diffuse large B-cell lymphoma may become important for therapeutic decision-making, as has already been demonstrated in several recent studies. 7,8,10 The germinal center B-cell-like and activated blood B-cells-like subgroups cannot be reliably distinguished by morphology alone.…”
mentioning
confidence: 96%
“…3,[6][7][8][9] Therefore, the molecular subtyping of diffuse large B-cell lymphoma may become important for therapeutic decision-making, as has already been demonstrated in several recent studies. 7,8,10 The germinal center B-cell-like and activated blood B-cells-like subgroups cannot be reliably distinguished by morphology alone. For example, the immunoblastic and centroblastic morphological variants of diffuse large B-cell lymphoma, particularly those with a polymorphic centroblast-like cells and/or a higher content of immunoblasts, are more commonly seen in the activated blood B-cellssubgroup but are also observed in the germinal center B-cell-subgroup.…”
mentioning
confidence: 96%